Influência de protocolos de jateamento na rugosidade da superfície de uma cerâmica de zircônia tetragonal parcialmente estabilizada por ítria - Sarmento, Hugo Ramalho; Campos, Fernanda [UNESP]; de Sousa, Rafael Santiago; Alves, Maria Luiza Lima; Machado, João Paulo Barros; de Assunção e Souza, Rodrigo Othávio E. (APESB (Associacao de Apoio a Pesquisa em Saude Bucal), 2011)
Objective: To evaluate the influence of different air abrasion protocols on the surface roughness of an yttria-stabilized polycrystalline tetragonal zirconia) (Y-TZP) ceramic, as well as the surface topography of the ceramic after the treatment. Method: Fifty-four specimens (7.5×4×7.5mm) obtained from two ceramic blocks (LAVA, 3M ESPE) were flattened with fine-grit sandpaper and subjected to sintering in the ceramic system's specific firing oven. Next, the specimens were embedded in acrylic resin and the surfaces to be treated were polished in a polishing machine using sandpapers of decreasing abrasion (600- to 1,200-grit) followed by felt discs with 10μm and 3μm polishing pastes and colloidal silica. The specimens were then randomly assigned to 9 groups, according to factors particle and pressure(n=6): Gr1- control; Gr2- Al 2O 3(50μm)/2.5 bar; Gr3- Al 2O 3(110μm)/2.5 bar; Gr4- SiO 2(30μm)/2.5 bar; Gr5- SiO 2(30μm)/2.5 bar; Gr6- Al 2O 3(50μm)/3.5 bar; Gr7- Al2O3(110μm)/3.5 bar; Gr8- SiO 2(30μm)/3.5 bar; Gr9- SiO 2(30μm)/3.5 bar. After treatments, surface roughness was analyzed by a digital optical profilometer and the morphology was examined by scanning electron microscopy (SEM). Data (μm) were subjected to statistical analysis by Dunnett's test (5%), two-way ANOVA and Tukey's test (5%). Results: The type of particle (p=0.0001) and the pressure (p=0.0001) used in the air abrasion protocols influenced the surface roughness values among the experimental groups (ANOVA). The mean surface roughness values (μm) obtained for the experimental groups (Gr2 to Gr9) were, respectively: 0.37 D; 0.56 BC; 0.46 BC; 0.48 CD; 0.59 BC; 0.82 A; 0.53B CD; 0.67 AB. The SEM analysis revealed that Al 2O 3, regardless of the particle size and pressure used, caused damage to the surface of the specimens, as it produced superficial damages on the ceramic, in the form of grooves and cracks. Conclusion: Al2O3 (110 μm/3.5 bar) air abrasion promoted the highest surface roughness on the ceramics, but it does not mean that this protocol promotes better ceramic-cement union compared to the other air abrasion protocols.
Influence of air abrasion protocols on the surface roughness of an yttria partially stabilized tetragonal zirconia ceramic
Keywords: Aluminum oxide; Dental materials; Dental porcelain; Silicon dioxide; Surface properties